2005
DOI: 10.1016/j.jnoncrysol.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixed alkali on EPR and optical absorption spectra in mixed alkali borate xNa2O–(30−x)K2O–70B2O3 glasses doped with iron ions

Abstract: Electron paramagnetic resonance (EPR) and optical absorption studies of iron doped mixed alkali borate glasses, xNa 2 O-(30 À x)K 2 O-70B 2 O 3 (5 6 x 6 25) have been investigated as a function of alkali content to look for the Ômixed alkali effectÕ on the spectral properties of the glasses. The EPR spectra of all the investigated samples exhibit resonance signals which are characteristic of the Fe 3+ ions. The EPR spectrum exhibits an intense resonance signal at g = 4.02 ± 0.1, a moderately intense signal at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The observed UV bands at 220-230, 275-285, 310 nm in various glasses have been attributed to Fe 3 + ions usually present in tetrahedral condition by most authors [30,31]. However, recent studies [32][33][34] have revealed that the Fe 3 + ions can also be present in octahedral sites. This controversy needs still further work to specify the exact coordination of the trace iron impurity present.…”
Section: Interpretation Of the Origin Of Uv-near Visible Absorption Imentioning
confidence: 99%
“…The observed UV bands at 220-230, 275-285, 310 nm in various glasses have been attributed to Fe 3 + ions usually present in tetrahedral condition by most authors [30,31]. However, recent studies [32][33][34] have revealed that the Fe 3 + ions can also be present in octahedral sites. This controversy needs still further work to specify the exact coordination of the trace iron impurity present.…”
Section: Interpretation Of the Origin Of Uv-near Visible Absorption Imentioning
confidence: 99%
“…Although studies on iron in glass have attracted the attention of the majority of scientists interested in transition metal behavior in various glasses, yet much recent work by Sreekanth Chakradhar et al [16,17] have postulated that Fe 3+ ions exhibit an octahedral symmetry in contradiction with most previous published works. It is (471) evident, therefore, that further studies are still needed by different recent techniques to justify the exact coordination of both iron states in various glasses.…”
Section: Introductionmentioning
confidence: 94%
“…The majority of Fe ions are believed by many authors to occupy tetrahedral network-forming sites in silicate glasses [10,11,14], although this has been disputed. Conversely, the majority of Fe 2+ ions are thought to occupy octahedral network--modifying sites [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The EPR spectrum of transition metal ions in phosphate glasses is an interesting research subject and affords a method to investigate the glass structure. EPR spectra of Fe 3 + ions in various glasses have been extensively studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is reported that the trivalent iron ions can take two different coordination sites, i.e., either tetrahedral or octahedral sites in glasses.…”
Section: Introductionmentioning
confidence: 99%